Asthma in an Adult Female Vervet Monkey (Chlorocebus sabaeus) - Köster, Liza S (Comp Med, 2016)
A 9-y-old, colony-bred, female vervet monkey (Chlorocebus sabaeus) presented with a 6-y history of open-mouth breathing, tachypnea, and sibilant wheezing. These symptoms did not significantly affect her activity or quality of life. Thoracic radiographs and results of bronchoalveolar lavage supported the diagnosis of asthma. Treatment comprising intramuscular prednisolone (tapered over 2 mo from twice daily to every other day), inhaled salmeterol–fluticasone (25 µg–250 µg per actuation twice daily) by mask, and a metered dose inhaler was successful in restoring a normal respiratory pattern. Despite the availability of several primate models of human asthma, this case represents the first report of spontaneous asthma in a NHP.